2021
DOI: 10.1108/rpj-07-2020-0174
|View full text |Cite
|
Sign up to set email alerts
|

Advances in additive manufacturing of shape memory polymer composites

Abstract: Purpose A review on additive manufacturing (AM) of shape memory polymer composites (SMPCs) is put forward to highlight the progress made up to date, conduct a critical review and show the limitations and possible improvements in the different research areas within the different AM techniques. The purpose of this study is to identify academic and industrial opportunities. Design/methodology/approach This paper introduces the reader to three-dimensional (3 D) and four-dimensional printing of shape memory polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 139 publications
(195 reference statements)
0
16
0
1
Order By: Relevance
“…Conversely, carbon-based materials (e.g., carbon black, carbon nanotubes (CNTs), carbon nanofibers, and graphene) provide excellent mechanical properties and electrical conductivity at much lower concentrations due to their outstanding specific surface area and aspect ratio, which makes them the most attractive fillers for the development of conductive SMPCs. [16,24] The fabrication of electro-activated SMPCs embedding carbon-based fillers have been explored by means of different 3D-Printing technologies, [25] ranging from Spray Deposition Modeling, [26] solvent-cast 3D-Printing, [27] Direct Ink Writing (DIW) [28,29] to Fused Deposition Modeling (FDM). [17,[30][31][32] Nevertheless, just one study has been found on 3D printed selectively electro-activated SMPCs embedding carbon-based fillers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, carbon-based materials (e.g., carbon black, carbon nanotubes (CNTs), carbon nanofibers, and graphene) provide excellent mechanical properties and electrical conductivity at much lower concentrations due to their outstanding specific surface area and aspect ratio, which makes them the most attractive fillers for the development of conductive SMPCs. [16,24] The fabrication of electro-activated SMPCs embedding carbon-based fillers have been explored by means of different 3D-Printing technologies, [25] ranging from Spray Deposition Modeling, [26] solvent-cast 3D-Printing, [27] Direct Ink Writing (DIW) [28,29] to Fused Deposition Modeling (FDM). [17,[30][31][32] Nevertheless, just one study has been found on 3D printed selectively electro-activated SMPCs embedding carbon-based fillers.…”
Section: Introductionmentioning
confidence: 99%
“…[33] In this regard, the lack of photocurable SMP, the high viscosity of the doped formulations, and the light scattering induced by the filler are the main limitations to the fabrication of SMPCs via SLA/DLP processes. [25] Trying to fill this gap, we report in this study the development of novel electro-activated SMPCs consisting of a photocurable and DLP printable SMP matrix embedding multi-walled CNTs. The optimization of the formulation and the study of its printability, together with the analysis of the electro-thermal properties of the material, enabled the preparation of electrically controllable DLP printed SMPCs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4D printing is expected to bring breakthrough improvements in several domains, such as robotics, sensors, and biomedicine [21][22][23]. In polymeric 4D printing, smart materials, either neat polymers or composites, must possess one or more functions that can be activated by physicochemical stimuli including, solvents [24,25], light [26][27][28], temperature [29][30][31][32][33],…”
Section: Introductionmentioning
confidence: 99%